Proof of Credibility: A Dynamic Consensus Framework for Blockchain Applications - Jalpa, Khamar; Patel, Hiren (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Blockchain is a technology for decentralized data management that was first created for Bitcoin. It is well-liked because of its security, anonymity, and data integrity. Blockchain peers are able to agree thanks to various algorithms. Nevertheless, validatorstatus, latency, and node failure factors are found to be absent from so many current systems. Traditional consensus mechanisms often solely consider technical specifications or stake, neglecting the reputation and credibility of validators. This can lead to malicious actors or less credible validators participating in the network, potentially compromising its integrity and stability. Also, slow transaction processing speeds can hinder user experience and limit blockchain applicability in fast-paced scenarios. Optimizing consensus mechanisms for speed while maintaining security and accuracy remains a significant challenge. Blockchain resilience hinges on its ability to withstand node failures without compromising data integrity or transaction processing. Existing approaches may not adequately address potential failure scenarios, leading to network disruptions and compromised trust. Our novel Proof of Credibility (PoC) tackles key gaps in existing consensus mechanisms, like validator reputation and latency. PoC prioritizes trustworthy validators and optimizes performance, making it ideal for crucial sectors like finance and smart contracts. By analyzing existing mechanisms and their variables like energy consumption and network size, we unveil optimization potential for a new generation of secure, scalable, and future-proof blockchains.